2015
DOI: 10.1016/j.jlp.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Vent burst pressure effects on vented gas explosion reduced pressure

Abstract: The overpressure generated in a 10L cylindrical vented vessel with an L/D of 2.8 was investigated, with end ignition opposite the vent, as a function of the vent static burst pressure, P stat , from 35 to 450 mb. Three different K v (V 2/3 /A v ) of 3.6, 7.2 and 21.7 were investigated for 10% methane-air and 7.5% ethylene-air. It was shown that the dynamic burst pressure, P burst , was higher than P stat with a proportionality constant of 1.37. For 10% methaneair P burst was the controlling peak pressure for K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Once the flame exits the vessel this will ignite any vented flammable gas not diluted by the atmosphere in its wake. The external explosion is often more severe than the internal explosion and there are many factors that can contribute to the severity, such as vent size (Bauwens et al, 2010) and vent burst pressure (Fakandu et al, 2015). The internal gas concentration before ignition can have an effect; rich mixtures often result in more severe explosions as there is more fuel available for combustion (Gill et al, 2016) and the opposite is true of lean mixtures.…”
Section: Nomenclature Tmentioning
confidence: 99%
“…Once the flame exits the vessel this will ignite any vented flammable gas not diluted by the atmosphere in its wake. The external explosion is often more severe than the internal explosion and there are many factors that can contribute to the severity, such as vent size (Bauwens et al, 2010) and vent burst pressure (Fakandu et al, 2015). The internal gas concentration before ignition can have an effect; rich mixtures often result in more severe explosions as there is more fuel available for combustion (Gill et al, 2016) and the opposite is true of lean mixtures.…”
Section: Nomenclature Tmentioning
confidence: 99%
“…Their findings showed that the maximum pressure does not increase monotonically with the vent failure pressure under central and rear ignition. The same vessel was employed by Fakandu et al [4] to investigate the effect of vent burst pressure on the maximum reduced explosion pressure of methane air and ethylene air mixtures. They observed that the dominant peak pressure depends on both the vent burst pressure and the vent coefficient K ( where V is the vessel volume and A v is the vent area).…”
Section: Introductionmentioning
confidence: 99%
“…Since early 1970s, numerous analytical models, empirical correlations (Bradley and Mitcheson, 1978;Cooper et al, 1986;Molkov, 1999;Tamanini, 2001) and engineering guidelines (NFPA-68, 2007(NFPA-68, , 2013 have been developed to estimate the vented explosion pressure. More recent studies have also been extensively conducted to better understand the turbulent flame acceleration and combustion inside the chamber (Chao et al, 2011;Fakandu et al, 2015;Tomlin et al, 2015;Bao et al, 2016;Qi et al, 2016) However, compared to the studies on internal pressure of vented explosion, combustion outside the enclosure has received little attention, although it could also be destructive to adjacent/far end structures (Palmer and Tonkin, 1980). The external gas explosion can occur simultaneously or earlier before the flame emerges from the enclosure, which eventually increase the peak pressure (Solberg et al, 1980;Schildknecht and Geiger, 1983).…”
Section: Introductionmentioning
confidence: 99%